Pemanfaatan E-Commerce Dan AI Dalam Meningkatkan Penjualan Digital UMKM - Umi Hayati; Martanto; Ahmad Rai Fatkaozi; Alfira Ayu Febrian Lesmana (AMMA : Jurnal Pengabdian Masyarakat, 2024)
Micro, Small and Medium Enterprises (MSMEs) play an important role in the Indonesian economy. However, the main challenge faced is the low adoption of digital technology in marketing and business operations. This study aims to analyze the empowerment of MSMEs through the use of e-commerce and artificial intelligence (AI) in increasing digital sales. The research method used is literature study and secondary data analysis from various trusted sources. The results show that the adoption of e-commerce allows MSMEs to expand market reach, improve operational efficiency, and increase interaction with customers. Meanwhile, the application of AI in MSME businesses can improve customer experience through service personalization, business process automation, and more accurate data analysis for decision-making. Although the utilization of these technologies has many benefits, challenges such as limited digital literacy, technological infrastructure, and access to capital are still the main obstacles for MSMEs in adopting e-commerce and AI optimally. Therefore, support is needed from various parties, including the government, academia, and the private sector to provide training and assistance in the implementation of digital technology for MSMEs. Thus, MSMEs can improve their competitiveness and contribute more to national economic growth.